Extracellular PPM1A promotes mineralization of osteoblasts differentiation in ankylosing spondylitis via the FOXO1A‐RUNX2 pathway. Issue 5 (9th February 2023) - Weon, Subin; Jo, Sungsin; Nam, Bora; Choi, Sung Hoon; Park, Ye‐Soo; Kim, Yong‐Gil; Kim, Tae‐Hwan
Abstract: Protein phosphatase magnesium‐dependent 1A (PPM1A), serine/threonine protein phosphatase, in sera level was increased in patients with ankylosing spondylitis (AS). Preosteoblasts were differentiated actively to matured osteoblasts by intracellular PPM1A overexpression. However, it was unclear whether extracellular PPM1A contributes to the excessive bone‐forming activity in AS. Here, we confirmed that PPM1A and runt‐related transcription factor 2 (RUNX2) were increased in facet joints of AS. During osteoblasts differentiation, exogenous PPM1A treatment showed increased matrix mineralization in AS‐osteoprogenitor cells accompanied by induction of RUNX2 and factor forkhead box O1A (FOXO1A) protein expressions. Moreover, upon growth condition, exogenous PPM1A treatment showed an increase in RUNX2 and FOXO1A protein expression and a decrease in phosphorylation at ser256 of FOXO1A protein in AS‐osteoprogenitor cells, and positively regulated promoter activity of RUNX2 protein‐binding motif. Mechanically, exogenous PPM1A treatment induced the dephosphorylation of transcription factor FOXO1A protein and translocation of FOXO1A protein into the nucleus for RUNX2 upregulation. Taken together, our results suggest that high PPM1A concentration promotes matrix mineralization in AS via the FOXO1A‐RUNX2 pathway.